Water and Rock Chemistry Inform Our Understanding of the Deep Biosphere: Case Study in an Archaean Banded Iron Formation - Schuler, Cristopher J.; Briscoe, Lindsey J.; Alexander, Scott C.; Alexander, E. Calvin; Gralnick, Jeffrey A.; Santelli, Cara M.; Toner, Brandy M. (Frontiers in Earth Science, 2022)
Research into the deep biosphere requires an understanding of both the microbial community at a given site and the geochemical and hydrological factors that support that microbial community. To highlight the interplay between geochemistry and microbiology in these deep environments, we characterized the hydrogeologic and geochemical systems of a 2.7 Ga banded iron formation within the Canadian Shield in the Soudan Underground Mine State Park in Minnesota, USA, a site known to host a lithotrophic microbial community. Calcium-sodium-chloride brines, characteristic of deep groundwaters throughout the Canadian Shield, were found in the site with total dissolved solids as high as 116,000 ppm in one borehole. Comparison of the Soudan waters to those found at other sites in the Canadian Shield or other sites of deep biosphere research indicate that they are notable for their high magnesium concentrations relative to total salinity. Additionally, the most saline Soudan waters have distinct 2H and 18O water isotope values suggesting long periods of isolation from the surface, which would allow for the evolution of a distinctive subsurface community. The presence of the banded iron formation along with the long-term isolation of the shield waters make Soudan a site of great potential for future research into deep crustal life. Furthermore, our work at Soudan highlights how geochemical data can inform future research into the deep biosphere and highlights a path for future research at the mine.